STRATEGI PEMASARAN JASA MELALUI BAURAN PEMASARAN UNTUK MENINGKATKAN KEPUASAN KONSUMEN (STUDY EMPIRIS HOTEL XYZ JAKARTA) - M J Renwarin, Joseph (Universitas muhammadiyah palembang, 2015)
This paper has aim to develop the marketing strategy in service businesses by marketing mix program. With the new international 5 (five) star hotel as the research object, the authors want to explore the research finding field and create some strategies for the management for improving their marketing strategies for sustain the competitive advantage. This paper use qualitative research for research explanatory and focus group discussion in several staffs and supervisors in sales and service department. The authors use many variables to know the relationship and the influence of independent variables namely the product, price, location, promotion, people, the process and physical facility to customer satisfaction. The authors disburse questionare to 100 respondents who fill in questioner participation.. The result of research shows that, t-test for each independent variable has an influence on customer satisfaction. The result of F-test shows that the F count of 59.992, this means that there is influencing together which are product, price, location, promotion, people, process and infrastructure, to customer satisfaction.